The use of multivariate statistical techniques in the assessment of river water quality - Dawood, Ammar; Faroon, Maha; Yousif, Yasameen (Anbar Journal of Engineering Sciences, 2020)
This study assessed the temporal and spatial water quality variability to reveal the characteristics of the Shatt Al-Arab River, Basrah, Iraq. A total of 14 water quality parameters (water temperature (T), pH, electrical conductivity (EC), Alkanets (Alk), total dissolved solids (TDS), turbidity (Tur), total hardness (TH), calcium (Ca), magnesium (Mg), chloride (Cl), sulphate (SO4), total suspended solids (TSS), sodium (Na), and potassium (k)) were analyzed Use of multivariate statistical methods in a total of three stations for the period 2016-2017. In this study was use a statistical approach to determine the water quality using the Pearson Correlation Index (PCI), Principal component analysis (PCA), and Factor Analysis (FA) were used to analyze the data. Main water pollutant sources were wastewater from agricultural drainage and industrial wastewater. Significant relationships recorded between the investigated parameters based on the results of PCI, at the 0.01 and 0.05 significance levels. Per the FA results, 77.1 % of the total variance explained by two factors.